Additive manufactured high-strength tungsten composite with high deformability by using a novel CoCrNi medium-entropy binder. (November 2022) - Chen, Hui; Li, Dan; Geng, Zhaowen; Wu, Yiyou; Zhang, Taomei; Jiang, Xue; Zhao, Siqi; Zhang, Hongbo; Han, Yong; Liu, Xiaochun; Chen, Chao
Abstract: Tungsten-based composites often exhibit good performance for high temperature applications, such as high strength, however, the very limited plasticity at room temperature becomes an intrinsic "Achilles' heel" due to the incompatible strain partition between different phases. In this work, an equiatomic CoCrNi medium-entropy alloy (MEA) was used as a novel binder to fabricate W–CoCrNi composites through laser metal deposition (LMD) technique. The microstructural features and corresponding mechanical properties were systematically investigated by changing the contents of CoCrNi binders. The intrinsic fast melting and high cooling rate followed by the cyclic thermal treatment during the additive manufacturing process induced a hierarchical microstructure: tens of micro-sized un-melted W particles were uniformly distributed in the CoCrNi matrix, while those partially melted W form supersaturate solid solution in the matrix with a W concentration of ∼20 wt% and finely dispersed Co7 W6 precipitates. With the increasing of CoCrNi, the morphology of Co7 W6 precipitates changes from coarse short rods into fine dendrites, which results in substantial increase in compression strain. The W-based composite shows an excellent combination of compression yield strength over 1300 MPa and strain of 60% at room temperature. The high strength derives from the capability of blocking dislocation motions by W particles and Co7 W6 precipitates, while the large plastic strain originates from the intrinsic high work hardening rate of CoCrNi MEA. The findings in this work provide an avenue for the design of refractory materials with high strength and high deformability by taking advantage of MEA binders. Graphical abstract: Image 1 Highlights: CoCrNi MEA was successfully introduced as a novel binder to fabricate the W–CoCrNi composites by laser metal deposition technique. The as-printed W–CoCrNi composites possessed high compressive yield strength and high strain-to-failure. Mechanisms of high strength, large plastic strain and work hardening capacity of the W–CoCrNi composites were revealed.